Effect of laser conditioning on nanoprecursor for improving laser damage resistance of HfO2 coatings. (8th February 2018) - Hu, Jianping; Zhou, Xin; Pan, Feng; Xu, Qiao
Abstract: An experimental and analytical approach is described to investigate the effect of laser conditioning on the nanoprecursor of the Hf cluster for improving the damage resistance of HfO2 coatings. Two test methods of 1-on-1 and R-on-1 (usually, R-on-1 is referred to as laser conditioning) were employed to measure the damage probabilities of samples of HfO2 coating. In addition, the measured damage probabilities of 1-on-1 and R-on-1 were compared with the simulations based on Mie scatter theory, heat transfer and damage probability calculation to determine the size distribution of the nanoprecursor of the Hf cluster, which indicates the decrease in their sizes. X-ray photoelectron spectroscopy analysis reveals that laser conditioning has increased the relative oxygen content, which implies that a portion of Hf atoms in the nanoprecursors are oxidized to HfO2 due to O atoms from the decomposed water and air, with a resulting decrease in their size and absorption and an increase in their laser damage threshold. The experimental and simulative results indicate that the size decrease and distribution variation of the Hf clusters may be another one of the mechanisms for laser conditioning to increase the damage resistance of HfO2 coatings.